Aetiological factors of hoarseness in patients attending at Kathmandu University Hospital (Bangladesh Journal of Otorhinolaryngology, 2013)
Objective: To evaluate the aetiological factors of hoarseness. Methods: This is a prospective, non- randomized and longitudinal study conducted from 1st august 2011 to 1st august 2012 in department of otorhinolaryngology of Kathmandu university Hospital, Dhulikhel, Nepal. All the patients with history of hoarseness underwent clinical examination, routine as well as special investigation to find the diagnosis. The final results were analyzed by simple manual analysis with frequency and percentage using Microsoft Excel software 2007. Results: There were total 280 patients included in the study. Among them the age groups of 21 30 years and 31 40 years were mainly suffer from hoarseness. Similarly, among 280 patients 200 (71.45%) were males whereas 80 (28.6%) were females with male to female ratio of 2.5:1.. The most common cause as per the distribution was acid peptic laryngitis with frequency of 37.8% whereas tuberculosis of larynx, papillary carcinoma of thyroid and papilloma of vocal cord accounts for only 0.4% each. Conclusion: There was etiological variation in hoarseness ranging from simple laryngitis to malignancies. So it is important not to ignore the hoarseness and precise history, examination and investigations should be done. DOI: http://dx.doi.org/10.3329/bjo.v19i1.11877 Bangladesh J Otorhinolaryngol 2013; 19(1): 14-17